Anxiety Contributing Factors in College Students during the Final Project: Ordinal Logistic Regression Analysis - Tiarawati, Ni Wayan; Yahya, Lailany; Adityaningrum, Amanda; Mahdang, Putri Ayuningtias; Arsad, Nikmatisni; Abdussamad, Siti Nurmardia; Payu, Muhammad Rezky Friesta; Nasib, Salmun K. (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The prevalence of anxiety disorders among university students is high, particularly during periods of high stress, such as when students are completing their final projects. This research aimed to investigate how self-confidence and anxiety levels relate among students working on their final projects at the Statistics Department at Universitas Negeri Gorontalo. Research was conducted on 86 students aged 21-26 years old using an online questionnaire. Self-confidence, self-efficacy, and social support were independent variables, while anxiety levels (mild, moderate, and severe) were dependent variables. Self-confidence was found to be significantly correlated with anxiety levels, while self-efficacy and social support were not significantly correlated. The result of ordinal logistic regression analysis indicated that students with high self-confidence were 0.13 times more likely to experience mild or moderate anxiety compared to those with moderate self-confidence. Those with high levels of self-confidence, however, are more likely to suffer from severe anxiety (26%) than those with moderate levels of self-confidence (4%). In certain academic situations, high self-confidence may not be a hindrance against anxiety. A more comprehensive understanding of anxiety will require further research considering additional factors that contribute to anxiety, factors that were not considered in this study.